Dimensi Sosial Budaya Bagi Keragaman Praktik Perawatan Kesehatan Penderita Malaria di Topoyo Provinsi Sulawesi Barat - Yahya - Kadir (Department Anthropology, Faculty of Social and Political Sciences Hasanuddin University., 2018)
The aim of the research was to describe and get understanding on health care practiced by community members infected or indicated infected by malaria in Topoyo District, Central Mamuju Regency, West Sulawesi Province. Using ethnographic approach, data was obtained through observation and in-depth interview. The study indicates that the community members infected or indicated infected by malaria not only to practice health care in various ways in overcoming malaria but also to mix the elements of treatment techniques derived from scientific medical tradition and local medical tradition. The variety and mixture of the health treatment is conditioned by the assumption that all types of medicines are powerful to cure illnesses. The cure of illnesses is determined by the compatibility of the drug and the blessing of God as the primary cause for the occurrence and cure of illnesses. It is also affected by different understandings, experiences, and information networks on malaria that are accessed by each actor and the attitude to respond illness.